2013
DOI: 10.1186/1297-9686-45-16
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics and phenotypic variability: some interesting insights from birds

Abstract: Little is known about epigenetic mechanisms in birds with the exception of the phenomenon of dosage compensation of sex chromosomes, although such mechanisms could be involved in the phenotypic variability of birds, as in several livestock species. This paper reviews the literature on epigenetic mechanisms that could contribute significantly to trait variability in birds, and compares the results to the existing knowledge of epigenetic mechanisms in mammals. The main issues addressed in this paper are: (1) Doe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
56
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 164 publications
(168 reference statements)
0
56
0
3
Order By: Relevance
“…Adaptive phenotypic plasticity may, however, involve modification of the epigenotype without change of the genomic structure of the organism, which may cause the neural, hormonal and/or enzymatic changes needed (Crews 2010, Nelson & Monteggia 2011. Epigenetic effects have been shown to be involved in the differentiation of cell lines and trigger altered gene ex pression (Jablonka & Raz 2009), and they can be induced by environmental temperature and contribute to adaptations to novel environments and be a source of phenotypic variation in ecological traits of fishes (Morán & Pérez-Figueroa 2011, Jonsson & Jonsson 2014) and other vertebrates (Frésard et al 2013, Burton & Metcalfe 2014, Varriale 2014.…”
Section: Discussionmentioning
confidence: 99%
“…Adaptive phenotypic plasticity may, however, involve modification of the epigenotype without change of the genomic structure of the organism, which may cause the neural, hormonal and/or enzymatic changes needed (Crews 2010, Nelson & Monteggia 2011. Epigenetic effects have been shown to be involved in the differentiation of cell lines and trigger altered gene ex pression (Jablonka & Raz 2009), and they can be induced by environmental temperature and contribute to adaptations to novel environments and be a source of phenotypic variation in ecological traits of fishes (Morán & Pérez-Figueroa 2011, Jonsson & Jonsson 2014) and other vertebrates (Frésard et al 2013, Burton & Metcalfe 2014, Varriale 2014.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to specifi c fl avors or odors can also modulate the olfactory system and taste preference in the offspring (Schaal et al 2000 ;Ong and Muhlhausler 2011 ;Todrank et al 2011 ). In certain bird species, females can load antibodies against encountered pathogens into the eggs' yolk, providing protection to their progeny (Frésard et al 2013 ). (3) Peri-and postnatally, the amount and quality of maternal care strongly infl uence the offspring's behavior in adulthood.…”
Section: Appendix 1: Experimental Methods To Examine Different Routesmentioning
confidence: 99%
“…Relevant researches on poultry epigenetics (Berghof, Parmentier, & Lammers, ; Feeney, Nilsson, & Skinner, ; Frésard et al., ; Gao et al., ; Leurox et al., ; Li, Guo, Zhang, Gao, & Guo, ; Li et al., ) revealed that epigenetic modifications may occur from the first stage of egg, when the mother provides an environmental signature through the egg content (Frésard et al., ). However, studies approaching the transgenerational epigenetic variance estimation (Jablonka, ; Jablonka & Raz, ; Lopes, Bastiaansen, Janss, Knol, & Bovenhuis, ; Varona et al., ) for economically important traits are still scarce in the literature.…”
Section: Introductionmentioning
confidence: 99%